Preliminary comparative analysis of kynurenine pathway metabolites in chronic ketamine users, schizophrenic patients, and healthy controls. (30th April 2020) - Zhang, Zhaohua; Zhang, Minling; Luo, Yayan; Ni, Xiaojia; Lu, Haoyang; Wen, Yuguan; Fan, Ni
Abstract: Objective: The serum kynurenine pathway metabolites kynurenic acid (KYNA), kynurenine (KYN), and tryptophan (TRP) were examined in chronic ketamine users and in schizophrenic patients. The correlations of the metabolites with sociodemographic data, clinical characteristics, and drug use status were analyzed. Methods: Seventy‐nine healthy controls, 78 ketamine users, and 80 schizophrenic patients were recruited. Serum TRP, KYN, and KYNA levels were measured by high‐performance liquid chromatography following tandem mass spectrometry (MS/MS). Psychotic symptoms were evaluated using the positive and negative syndrome scale (PANSS), the Beck Depression Inventory (BDI), and the Beck Anxiety Inventory (BAI). Results: Serum levels of TRP, KYNA, and KYN (in ketamine users only) were lower in ketamine users and schizophrenic patients than in controls ( p  < .05). TRP and KYN were lower in ketamine users than in schizophrenic patients ( p  < .01). KYNA levels were positively correlated with the current frequency of ketamine use in ketamine users ( p = .031), and serum KYNA levels were negatively correlated with the duration of schizophrenia ( p = .015). Conclusion: TRP, KYNA, and KYN were lower in chronic ketamine users than in controls, and the alterations were in the same direction as those observed in schizophrenic patients.